Perbandingan hasil belajar matematika peserta didik menggunakan pendekatan realistic mathematics education dengan pendekatan saintifik di SMP Negeri 14 Kota Bengkulu - Agung Wibowo; Hanifah Hanifah; Effie Efrida Muchlis (University of Bengkulu, 2019)
AbstraCT[Comparison of Student Learning Outcomes in mathematics using Realistic Mathematics Education Approach and Scientific Approach in SMP Negeri 14 Kota Bengkulu] The aim of this research was to find out whether student learning outcomes in mathematics using Realistic Mathematics Education (RME) approach better than student learning outcomes in mathematics using scientific approach in grade VII Junior High School Number 14 Bengkulu City academic year 2018/2019. The type of this research was Quasi Experiment Research with Nonequivalent Posttest-Only Control Group Design. The population of this research were all of student grade VII Junior High School Number 14 Bengkulu City academic year 2018/2019. The sample taken with cluster random sampling technique so that the class VII 5 was obtained as Realistics Mathematics Education (RME) approach class with 26 students and class VII 6 was obtained as scientific approach class with 26 students. The instrument of this research was student learning outcomes test sheet in an essay form. The average student lerning outcomes in mathematics using Realistic Mathematics Education (RME) approach is 53,5 and The average student lerning outcomes in mathematics using Scientific approach is 43,54. This research showed that student learning outcomes in mathematics using Realistic Mathematics Education (RME) approach better than student learning outcomes in mathematics using scientific approach in grade VII Junior High School Number 14 Bengkulu City, with tcount = 2,689441 > ttable = 2,008559. Keywords: learning outcomes in mathematics; realistic mathematics education (rme) approach; scientific approach. (Received September 4, 2019; Accepted September 26, 2019; Published October 8, 2019) AbstrakTujuan penelitian ini adalah untuk mengetahui apakah hasil belajar matematika peserta didik menggunakan pendekatan Realistic Mathematics Education (RME) lebih baik dari hasil belajar matematika peserta didik menggunakan pendekatan saintifik di Kelas VII SMP Negeri 14 Kota Bengkulu tahun pelajaran 2018/2019. Jenis penelitian ini adalah Quasi Experiment Research (Penelitian Eksperimen Semu) dengan desain penelitian nonequivalent Posttest-Only Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas VII SMP Negeri 14 Kota Bengkulu tahun pelajaran 2018/2019. Sampel diambil dengan menggunakan teknik cluster random sampling sehingga diperoleh kelas VII 5 sebagai kelas pendekatan Realistic Mathematics Education (RME) yang berjumlah 26 peserta didik dan kelas VII 6 sebagai kelas pendekatan Saintifik yang berjumlah 26 peserta didik. Instrumen dalam penelitian ini adalah lembar tes hasil belajar yang berbentuk soal uraian. Rata-rata hasil belajar matematika peserta didik dengan pendekatan Realistic Mathematics Education (RME) adalah 53,5 sedangkan rata-rata hasil belajar peserta didik dengan pendekatan Saintifik sebesar 44,54. Penelitian ini menunjukkan bahwa hasil belajar matematika peserta didik menggunakan pendekatan Realistic Mathematics educatio (RME) lebih baik dari hasil belajar matematika peserta didik menggunakan pendekatan Saintifik di kelas VII SMP Negeri 14 Kota Bengkulu, dengan . Kata kunci: hasil belajar matematika; pendekatan realistic mathematics education (rme); pendekatan saintifik.